Financial Development, Institutional Quality, and the Influence of Various Environmental Factors on Carbon Dioxide Emissions: Exploring the Nexus in China - Amin, Azka; Ameer, Waqar; Yousaf, Hazrat; Akbar, Muhammad (Frontiers in Environmental Science, 2022)
Carbon dioxide (CO2) emissions have been the key source of extreme environmental degradation and have adverse impact on climate and human activities. Although a large number of studies have explored the determinants of CO2 emissions, yet the role of institutional quality has not been fully studied. Our study contributes to the existing literature by examining the influence of financial development, institutional quality, foreign direct investment, trade openness, urbanization and renewable energy consumption on CO2 emissions over the period 1996-2020 by utilizing the dynamic ARDL simulations. The empirical findings of the study indicate that the indicators of governance, trade, financial development and renewable energy consumption adversely affect the CO2 emissions, while urbanization and foreign direct investment contributes to the environmental degradation. The empirical results of this study indicate that in order to mitigate environmental degradation and to achieve environmental sustainability, the government should establish the consistency between environmental and economic policies. Moreover, in order to achieve low carbon emissions and sustainable development, the countries need viable financial institutions that focus on green growth by promoting clean production process strategy to ensure the reduction of CO2 emissions.